Linking Performance, Policy, and Supervision to Revenue Growth in Public Roadside Parking Services: Evidence from Buleleng Regency - Adimahendra, Made Risky; Yudiaatmaja, Fridayana; Meitriana, Made Ary (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the effect of performance, policy, and supervision on retribution revenue in Buleleng Regency. Using a quantitative approach, data were collected from 110 employees of the local Department of Transportation responsible for managing public parking services. The study employed multiple linear regression analysis to test the influence of the independent variables—performance, policy, and supervision—on the dependent variable, retribution revenue. Reliability and validity tests confirmed that the research instruments were consistent and accurate. Classical assumption tests, including normality, multicollinearity, and heteroskedasticity, indicated that the regression model met the necessary criteria. The results of the t-test show that each independent variable has a significant positive effect on retribution revenue, with performance having the strongest influence, followed by supervision and policy. The F-test results further confirm that all independent variables collectively impact retribution revenue. The coefficient of determination (Adjusted R² = 0.647) indicates that 64.7% of the variance in retribution revenue can be explained by the independent variables, while the remaining 35.3% is influenced by other external factors. This study concludes that improving employee performance, implementing strategic policies, and enhancing supervision are essential for increasing retribution revenue. The findings provide practical implications for local government management and suggest directions for future research to include broader contexts, qualitative insights, and the integration of predictive analytics in revenue optimization.